Domestic Solid Waste Crusher - Khankelov, Tavbay; Tursunov, Shavkat; Maksudov, Zokir (International Journal of Psychosocial Rehabilitation, 2020)
The article gives an analysis of the types of collection and transportation of municipal solid waste, as well as the impact of the type of waste collection on the design of the crusher. In addition, the methods and methods, as well as the principles of the work of crushers for grinding food waste, are analyzed. The questions of determining and substantiating the basic parameters of a hammer mill using the basic principles of the theory of similarity and modeling are considered. To compile the criterion equation, the dimensional analysis method was used.